Promoting enterprise-led innovation in China - Zhang, Chunlin (Washington, DC World Bank, 2009)
This book explores policy options for China to implement its strategy of enterprise-led innovation. It identifies two sets of challenges facing China, and recommends actions along four dimensions: pursuing a balanced strategy, creating the right incentives, building capacity of the private sector, and strengthening the ecosystem for the venture capital industry.
Includes bibliographical references (p. 127-134) and index.
Keywords: Technological innovations--Economic aspects--China.